EDUCAHIV: avaliação da usabilidade de aplicativo móvel para a prevenção e controle do HIV/AIDS - BARROS, Kely da Silva (Universidade Federal do Pará, 2025)
Introduction: Aiming to achieve the 95-95-95 target recommended by the United Nations to end AIDS by 2030, the use of mobile health applications, also called mHealth (mobile health), has become a very useful technological equipment in the combating the HIV virus epidemic, as it is a universal and easily accessible tool. It was found that applications based on Ministry of Health Protocols are available in a fragmented manner and that there is no one that brings together all the necessary information and is aimed at nurses, making their daily clinical practice, which tends to meet diverse demands, difficult. Objective: To evaluate the usability of the “EducaHIV. Methodological Course: This is a methodological research, with usability evaluation carried out with nurses who work in Primary Health Care in the Administrative District of Guamá, municipality of Belém. The instrument used to evaluate the usability of the application was the SURE questionnaire ( Smartphone Usability questionnaiRE) which uses a 4-point Likert-type response scale and which also has its own result scale to evaluate usability, in addition, the Content Validity Index-CVI, the CVI of individual items, was calculated and the S-CVI/AVE which is the average of the I-CVI. Results: 17 nurses participated in the research who used the application for an average of 20 minutes using smartphones or tablets and, after using it, answered the printed SURE questionnaire with an average duration of 10 minutes. Data collection took place in a unique approach in October 2023. Data analysis showed that 94% of nurses obtained a usability level of 80 on the SURE scale, ensuring that the application was useful and also obtained a CVI of 0.92 and the S-CVI/AVE of 0.91. Regarding the considerations reported in the questionnaire, the most frequent was the need for the application to zoom to improve the visualization of the content and the insertion of information about drug interactions of antiretrovirals and other medications. Conclusion: Given the satisfactory results, it is concluded that the EducaHIV application has a high level of usability and a good agreement rate, which reflects on the quality of the application and user satisfaction.